KNOWLEDGE ATTITUDE AND PRACTICE OF EAR CAREIN SAUDI COMMUNITY - Osama Mansour Alateeq et al (Baqai Journal of Health Sciences)
Ear cleaning and removing the available wax out of them is one of the most widely spread habits among the different populations despite the harmful effect and consequences that could result. Ear wax is useful and protective for the human ears, and in normal cases it exists in healthy amounts inside the ear canal. Current study aims to investigate the knowledge, attitudes and practices of ear care among Saudi community members through studying a sample composed of 200 participants from both rural and urban populations. A self-administered questionnaire consisted of 15 items have been administered to the study groups. Findings of the study showed that there is a lack of knowledge and a high practice of incorrect habits, besides to the low awareness level among the rural population regarding ear care compared to the urban population. Study recommends that there is a need to perform more studies and increase the awareness of the community members towards the correct and healthy way of ear care